2001
DOI: 10.1093/humrep/16.5.918
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intracytoplasmic sperm injection and semen parameters on blastocyst development in vitro

Abstract: The present study compares the development and quality of blastocysts derived from conventional oocyte insemination with those derived from intracytoplasmic sperm injection (ICSI). Oocytes were collected from patients undergoing ovarian stimulation with human menopausal gonadotrophins for IVF. Patients with normal semen were assigned to conventional oocyte insemination while those with progressive motility <20% and/or normal sperm morphology < or =4% were assigned to ICSI. Resulting embryos were cultured for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 49 publications
6
69
1
1
Order By: Relevance
“…Apoptosis is a process that can be triggered by different intracellular and extracellular mechanisms [28,29]. Free radicals and ROS can trigger the chain of reactions that lead to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a process that can be triggered by different intracellular and extracellular mechanisms [28,29]. Free radicals and ROS can trigger the chain of reactions that lead to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since impaired semen quality may have a negative impact on the development of embryos, the influence of ICSI on blastocyst development is still a matter of debate. Some studies reported decreased blastocyst development [14,29] in ICSI than IVF embryos whereas others did not observe any difference [22,30]. Rienzi et al reported blastocyst formation rate as 44.8 % in ICSI cycles [30].…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that oocytes injected with spermatozoa with high motility have a significantly higher chance of reaching the blastocyst stage [30,43]. It has also been reported that paternal cigarette smoke exposure affects the embryonic implantation ability [21].…”
Section: Discussionmentioning
confidence: 99%